Knowledge regarding rabies among school children in an urban area of Kancheepuram district: a cross sectional study - Grace G., Angeline; S., Gopalakrishnan; Edward, Shanthi (International Journal Of Community Medicine And Public Health, 2020)
Background: Out of ten people who die due to rabies, four of them are children. Awareness regarding the disease is important to bring down the rabies mortality among children. This study was planned to assess the knowledge regarding rabies among high school students in an urban area of Kancheepuram district. Methods: This study was a school based cross sectional study done in chrompet, an urban area in Kancheepuram district. All students studying in IX and X standards in a school chosen by simple random sampling method were included in the study. Sample size of 335 was calculated using the formula 4pq/l2 and adjusting for 10% non-response. Data was collected using a pre-tested, structured questionnaire and analysed using SPSS version 22.0. Knowledge score of >50% was taken as “adequate knowledge”. Results: Out of the total 340 respondents, 189 (55.6%) were girls and 151 (44.4%) were boys. Around 23.5% reported having pets at home. Though 97.6% of children were aware that dog is an important reservoir of rabies, only 46% knew that the disease is caused by a virus. About 25.6% had knowledge about other reservoirs of rabies. About 72% knew about prevention through anti-rabies vaccine but only 31.5% were aware of the vaccine availability in government hospitals. Overall adequate knowledge on rabies was noted in 46.2% of respondents. Conclusions: Children’s understanding on the cause of rabies, prevention and control of rabies was inadequate. Health education activities need to be promoted for the school students to improve their level of awareness on rabies.